2021
DOI: 10.1186/s12931-021-01735-7
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain from early to middle adulthood increases the risk of incident asthma later in life in the United States: a retrospective cohort study

Abstract: Background Data describing the effects of weight change across adulthood on asthma are important for the prevention of asthma. This study aimed to investigate the association between weight change from early to middle adulthood and risk of incident asthma. Methods Using data from the National Health and Nutrition Examination Survey (NHANES), we performed a nationally retrospective cohort study of the U.S. general population. A total of 20,771 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Secondly, they used different reference groups, included different number of cases and there were also some differences in the definitions of weight change patterns 14 . Wang et al found the risk of developing asthma increased 1.61 and 1.43 in the non-obese to obese group and the stable obese group, respectively by using the data from NHANES (1999–2016) 15 . Their study focused on obese participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, they used different reference groups, included different number of cases and there were also some differences in the definitions of weight change patterns 14 . Wang et al found the risk of developing asthma increased 1.61 and 1.43 in the non-obese to obese group and the stable obese group, respectively by using the data from NHANES (1999–2016) 15 . Their study focused on obese participants.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we divided the absolute weight changes into five groups: weight loss > 2.5 kg, weight change within 2.5 kg (the absolute weight loss or weight gain ≤ 2.5 kg), 2.5 kg < weight gain ≤ 9.9 kg, 10 kg ≤ weight gain ≤ 19.9 kg, and weight gain ≥ 20.0 kg, weight change within 2.5 kg was used as the reference group. We chose these categories for comparison with the previous studies 15 , 36 38 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the available studies have reported a dose–response relation between increasing BMI and asthma incidence, but studies have differed somewhat with regard to what BMI level risk of asthma starts to increase 6 21 . Fewer studies have been published on other measures of adiposity and risk of asthma, but four studies reported increased asthma risk with increasing waist circumference 7 , 11 , 13 , 21 , while three studies reported an increased risk with greater weight gain 10 , 16 , 22 , and a fourth study found no clear association 18 . In contrast, studies have generally reported no association between weight loss and asthma 10 , 16 , 18 , 22 .…”
Section: Introductionmentioning
confidence: 99%